2023
DOI: 10.1155/2023/3781091
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast Risk Model for Prediction of Colorectal Carcinoma Prognosis and Therapeutic Responses

Abstract: Colorectal carcinoma (CRC) is a malignant tumor of the digestive system. Cancer-associated fibroblasts (CAFs) are important cellular elements in the tumor microenvironment of CRC, which contribute to CRC progression and immune escape. To predict the survival outcome and therapeutic responses of CRC patients, we identified genes connected with stromal CAF and generated a risk model. In this study, we used multiple algorithms to reveal CAF-related genes in the Gene Expression Omnibus and The Cancer Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[ 37,38 ] The genes included in their models were as follows: PTGER2, FGF2, IGFBP3, ANGPTL4, DKK1, WNT16, SPP1, ZNF532, COLEC12, DPP7/2, YWHAB, MCM4, FBXO46, GLP2R, VSTM2A, and so on. [ 37,39,40 ] In our model, we included directly nine key EIOGs, and finally got a mode with the highest AUC reached 0.788, which indicated that EIOS alone play an important role in the CRC progression. We also proposed that a better prognostic model could be established based on a comprehensive understanding all these genes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37,38 ] The genes included in their models were as follows: PTGER2, FGF2, IGFBP3, ANGPTL4, DKK1, WNT16, SPP1, ZNF532, COLEC12, DPP7/2, YWHAB, MCM4, FBXO46, GLP2R, VSTM2A, and so on. [ 37,39,40 ] In our model, we included directly nine key EIOGs, and finally got a mode with the highest AUC reached 0.788, which indicated that EIOS alone play an important role in the CRC progression. We also proposed that a better prognostic model could be established based on a comprehensive understanding all these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating fibroblasts, known as CAFs, are an important component of the TME. Currently, they are increasingly being paid attention to in the context of cancer progression because they extensively infiltrate cancerous tumors, which is connected with a bad prognosis [137,138]. CAFs are a valuable source of extracellular matrix components and proteolytic enzymes (metalloproteinases).…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%